User experience assessment on websites and mobile applications of movie vendors in Singapore - Chee, Zion Wei Xiang (2017)
A user experience assessment and comparison of online movie booking system in websites and mobile applications among different movie vendors in Singapore. The objective of this project was to learn and acquire the relevant knowledge and skills to be able to make an accurate and comprehensive user experience assessment.